2017
DOI: 10.1149/2.0251708jss
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Free Vacancy Disordering (IFVD) of InGaAs/AlGaAs Quantum Well Laser Structures

Abstract: Impurity free vacancy disordering (IFVD) has been used to investigate the atomic interdiffusion of InGaAs/InGaAs quantum well laser structures using double-crystal X-ray diffraction (DCXRD) and photoluminescence measurements. X-ray measurements showed that some part of the carbon was electrically activated after annealing without a dielectric capping layer, but not after annealing with a TiO2 capping layer. For a SiO2 capping layer, the tensile peak was still observed after annealing which is comparable to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It can also be observed that the unnormalized PL intensity signal of all the annealed coating samples became weaker. Firstly, group III vacancies were created at the GaAs–SiO 2 interface due to the out-diffusion of Ga atoms into the dielectric capping layer [ 16 ]. The group III vacancy diffused into the QW region, promoted the atomic interdiffusion between the barrier and the well, and therefore, led to the PL peak shift toward the higher-energy side.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be observed that the unnormalized PL intensity signal of all the annealed coating samples became weaker. Firstly, group III vacancies were created at the GaAs–SiO 2 interface due to the out-diffusion of Ga atoms into the dielectric capping layer [ 16 ]. The group III vacancy diffused into the QW region, promoted the atomic interdiffusion between the barrier and the well, and therefore, led to the PL peak shift toward the higher-energy side.…”
Section: Resultsmentioning
confidence: 99%
“…Although the majority of researchers have demonstrated that strain-enhanced interdiffusion is an efficient strategy to expand the QW emission wavelength range, recently, some of them also consider that strain-introduced crystal defects could improve the intermixing diffusion rate to some extent [ 15 , 16 ]. However, the exact working mechanism is still controversial.…”
Section: Introductionmentioning
confidence: 99%